The Effectiveness of Project-Based Learning in Improving Students' Critical Thinking Skills - Dewi, Dewi; Mukaromah, Ayu; Ilham, Muhammad; Arifin, Zaenal (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of project-based learning (PjBL) in improving students' critical thinking skills. Using a qualitative approach with a case study design, data were collected through participant observation, in-depth interviews with students and teachers, and analysis of learning documents. The results showed that PjBL significantly contributed to improving students' critical thinking skills, particularly in the aspects of information analysis, argument evaluation, and knowledge synthesis. Key findings revealed that the contextual and inquiry-oriented characteristics of PjBL were able to create learning experiences that encouraged students to actively engage in the process of inquiry, critical discussion, and authentic problem solving. Key factors for successful implementation included: (1) project design relevant to real life, (2) the role of teachers as effective facilitators, and (3) a collaborative learning environment. Identified obstacles were primarily related to students' readiness to manage independent projects and the need for appropriate scaffolding. Theoretically, these findings strengthen the constructivist basis of learning and emphasize the importance of a student-centered approach for the development of higher-order thinking skills. This study recommends the integration of PjBL into the curriculum by considering teacher training needs and adjusting implementation strategies according to the learning context. The research implications highlight the potential of PjBL as an innovative learning model to prepare students to face complex 21st century challenges.